Transnationals and governments : recent policies in Japan, France, Germany, the United States, and Britain - Bailey, David, 1966- (Routledge, 1994)
Because of the potential ease with which transnational corporations can relocate, there has been a tendency for many governments to avoid direct attempts to intervene in their activities. Nonetheless, the major economies have adopted a wide range of policies towards transnational corporations. Some (Japan and France in particular) have been very concerned by the impact of such firms. Others (most notably Britain) have had a relatively relaxed attitude.